U.S.-RUSSIA RELATIONS IN THE SPHERE OF CYBERSECURITY - Mikiashvili, Salome (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the purpose of the study is to critically evaluate US cyber security policy using a qualitative and comparative approach, the disadvantages that the country faces in the sphere of Cyber Security and identify what mechanisms and developments will Improve Cyber Security Policy to help overcome the challenges in response to Russian Cyberaggression. The methodological basis of the research comprises philosophical, ideological, general scientific and special methods. Results: cybercrime is recognized as the most threatening and dangerous crime of the 21st century, the more the consumer relies on information and communication technologies, the more cyber threats increase thus becoming greatest threat for countries national defense. Also there is lack of regulation in cyberwar that constitutes global threat. The author exemines the effectivness of the measures taken by the US and EU countries taken during or after the attacks. Discussion: improvement of the National Cyber defense strategy, search for actions to be taken while dealing with cyber attacks.